2012
DOI: 10.1098/rspb.2012.1403
|View full text |Cite
|
Sign up to set email alerts
|

Plant-ants use symbiotic fungi as a food source: new insight into the nutritional ecology of ant–plant interactions

Abstract: Usually studied as pairwise interactions, mutualisms often involve networks of interacting species. Numerous tropical arboreal ants are specialist inhabitants of myrmecophytes (plants bearing domatia, i.e. hollow structures specialized to host ants) and are thought to rely almost exclusively on resources derived from the host plant. Recent studies, following up on century-old reports, have shown that fungi of the ascomycete order Chaetothyriales live in symbiosis with plant-ants within domatia. We tested the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 17 publications
2
59
0
2
Order By: Relevance
“…In addition, a recently described species, Arthrocladium tardum (Trichomeriaceae), has been isolated both from a domatium of Leonardoxa africana occupied by the ant Petalomyrmex phylax in Cameroon and from decaying coconut shells in Brazil [6]. Although some Chaetothyriales strains are clearly mutualistic symbionts of ants [28,33,34], our study indicates that ant nests can be colonized by opportunistic species and that Chaetothyriales taxa might display exceptional dispersal capacities and surprising ubiquity. In the future, it will be most useful to investigate the degree of specialization of the interactions between particular ant and fungal partners in order to interpret the phylogenetic pattern in evolutionary terms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, a recently described species, Arthrocladium tardum (Trichomeriaceae), has been isolated both from a domatium of Leonardoxa africana occupied by the ant Petalomyrmex phylax in Cameroon and from decaying coconut shells in Brazil [6]. Although some Chaetothyriales strains are clearly mutualistic symbionts of ants [28,33,34], our study indicates that ant nests can be colonized by opportunistic species and that Chaetothyriales taxa might display exceptional dispersal capacities and surprising ubiquity. In the future, it will be most useful to investigate the degree of specialization of the interactions between particular ant and fungal partners in order to interpret the phylogenetic pattern in evolutionary terms.…”
Section: Discussionmentioning
confidence: 89%
“…Fungal patches also contain nematodes, bacteria and spores of opportunistic fungi [30][31][32]. Detailed functional investigation of a few systems revealed that domatia patches are manured and used as a food source by the ants [33,34] in a way reminiscent of fungal culture by attine ants. Ants and plants living in symbiosis are scattered throughout their respective phylogenies and have evolved many times independently, at least 40 and 158 times in their respective lineages [24,35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found intimate cofeeding relationships between Chaetothyriales fungi and plant-ants, in which the ants fertilize the fungi and also consume it [11,44]. In other ant-plant symbioses, there has been some evidence for distinct fungal communities associated with different ant species (e.g.…”
Section: ) Ellipses Indicate 80% Confidence Intervals (Ci)mentioning
confidence: 99%
“…Hemipterans were early and enduring models for studying how animals can obtain such key nutrients from microbes [9], but the broad relevance of bacteria and fungi as potential sources of nutrition for ants, which are typically omnivorous, was recognized only recently [10,11]. Most phloem-feeding hemipterans are associated with just one or a few highly specialized intracellular bacteria that are vertically transmitted, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Ants also interact with Chaetothyriales fungi, either as part of the carton nest building process where arboreal ants use fungal hyphae to strengthen the nest or trap insects ([30,85], figure 1m) Chaetothyriales seem to be cultivated by ants and are involved in a complex trophic mutualism where the ants (especially larvae) feed on the fungi, which they actively fertilize by defecation [86], and the fungi play a role in nutrient recycling as well as facilitating nutrient uptake by breaking down materials [87]. In this special feature, Vasse et al [88] show that ant/Chaetothyriales interactions evolved multiple times and that carton nest fungi and domatium fungi form different lineages.…”
Section: Ant Interactions With Fungimentioning
confidence: 99%